Analysis of punctuation error in one author of alternate universe on Twitter - Jumyanti Jumyanti; Ernie D.A. Imperiani (Passage: Journal of English Language and Literature, 2023)
This study analyzes the punctuation errors found in the three AUs titles belonging to one author on Twitter. Particularly, this study aims to determine what types of errors appear in the three AUs and what factors cause the errors. The data for this study were obtained from the author's Twitter account entitled Happy Birthday, Kai, Celebrity Crush, and Illustrious. Furthermore, the study used a qualitative case study design to identify the punctuation error found in AU on Twitter and the types of errors by using the theory of Burt, Dulay, Krashen (1982). Meanwhile, the factors of occurrence of errors were examined by using the theory of Brown (1994). The results revealed that the author made three types of errors: omission, addition, and misinformation. The most dominant type that appeared was omission 19 times. Then, these three types of errors arise due to 2 factors: the intralingual error factor and the context of learning factor. Nevertheless, these three AUs still have many readers and receive many likes. However, correct punctuation is considered necessary because it can affect the reader's understanding.